ASSESSMENT OF THE TECHNIQUES USE TO HARVEST BURITI FRUITS (Mauritia flexuosa L.f.) IN THE DISTRICT OF JENARO HERRERA, LORETO, PERU - FALEN HORNA, Lourdes Yesenia (2018)
The buriti is a palm of high commercial value, with ecological and social importance in the Peruvian Amazon. The excessive felling of the female individuals for the use of the fruits has caused that the fruit harvest is carried out at greater distances from the population centres and has triggered the degradation and low state of conservation of the natural palm swamps. The objective of this study was to evaluate how the inhabitants are adapting to the degradation of the resource, through the implementation of techniques of sustainable use of buriti fruits. We applied semi-structured surveys to 35 aguaje harvesters, evaluated 17 harvesting areas and accompanied 8 harvesters in the use of the buriti fruits of 16 adult individuals. The results show that the inhabitants of the district of Jenaro Herrera have implemented harvesting techniques that prevent the death of female plants less than 20 meters height, that is, they make sustainable use of the resource. In addition, the cultivation of the species in the farms and orchards demonstrates the concern of the inhabitants to keep this resource closer to the population centres. These activities demonstrate the ability of local people to adapt to the scarcity of buriti fruits. Therefore, the willingness to manage the resource generates new opportunities for the conservation and sustainable management of the buriti, thus ensuring the supply of demand.